Measuring consumers attitudes towards health and taste and their association with food-related life-styles and preferences. (April 2019) - Saba, A.; Sinesio, F.; Moneta, E.; Dinnella, C.; Laureati, M.; Torri, L.; Peparaio, M.; Saggia Civitelli, E.; Endrizzi, I.; Gasperi, F.; Bendini, A.; Gallina Toschi, T.; et al.
Highlights: The original three-factor model of the Taste scale of the HTAS was not confirmed. The Health scale was effective in differentiating subjects according to their healthy attitudes by clustering. Attitudes towards health are positively associated with liking and familiarity with healthy diet. More interest in convenience increased the probability to be less interested in health. More interest in product information and food quality increased the probability to be more interested in health. Abstract: The purpose of the current study, was to apply and validate the factor structure of the Health and Taste Attitude Scales in an Italian adult sample of 1224 subjects, recruited on a national basis in order to characterise consumers' food-related attitudes with weak and strong connotations of health and taste. Both exploratory and confirmatory factor analysis were used to evaluate the factor structure of the three sub-scales of Health (General health interest, Light product interest, Natural product interest) and three sub-scales of Taste (Craving for sweet foods, Using foods as a reward, Pleasure). Results showed that the internal structure was similar to the theoretical proposal, with two exceptions for the Taste scale. The Pleasure sub-scale presented strong problematic loadings and consequently was removed from the model. The Craving for sweet foods sub-scale was split into two new underlying constructs describing attitudes towards craving for sweet food based on their own experience and attitudes towards other-people's craving. The three Health sub-scales were used as a basis for the derivation of consumers clusters. Three groups of subjects with different interest in food-related health (Low, Medium, and High Interest) were identified. This segmentation confirmed an association between positive attitudes towards health and liking and familiarity with selected food groups. People more convenience-oriented and less interested in product information and food quality had higher probability to have a lower interest in food-related health. Subjects with higher positive attitudes towards using foods as a reward had a higher probability to belong to the cluster with lower interest in food-related health.